On Non-epistemic Values in Climate Science for Decision Support - Lee, Jessica (Department of Philosophy, 2022)
Climate change is an ever-increasing threat to humanity, making the need for decision relevant, actionable climate science more and more pressing. With this need comes pressure to articulate what constitutes responsible practice in climate science for decision support. This requires in part understanding the role that values should play in socially relevant science. My aim in this thesis is to develop a deeper understanding of the role of non-epistemic values in climate science for decision support. To achieve this, I bring philosophical discussions of values in science into conversation with elements that are particular to climate science as a practice. I begin by drawing on work by philosophers of science to argue for three ways in which values can be good for science: they can help scientists meet their moral obligations through managing inductive risk; they can promote the multiple aims of research; and the presence of diverse values can promote objectivity. I apply these arguments in the context of climate science for decision support and present a range of examples to show where in the scientific process values can appropriately inform choices that climate scientists make. I then identify and examine three important value-related conflicts that can arise, even when conditions seem right for values to influence choices in science. These conflicts, which have been largely overlooked in philosophical work, include conflicts between epistemic and social values; conflicts related to the multiple roles that scientists might occupy in society; and conflicts between personal values and community values taken to regulate scientific practice. I argue that these conflicts have the potential to make value-based choices difficult to resolve. Some commentators have recently raised the possibility that when value-based disagreements arise climate science could be more like medicine in its management of risk. I take this suggestion seriously and conclude by proposing that climate scientists ought to explicitly embrace some nonepistemic values, such as human security, as constitutive of their field. I respond to potential objections to this proposal, arguing that it would not be a radical change to science, that it would not undermine science's epistemic integrity, and that it need not result in the promotion of politically contentious values. I then discuss how embracing non-epistemic values as constitutive of the field could have implications for practice and could contribute to the development of a code of ethics for climate scientists.